Effects of early childhood otitis media and ventilation tubes on psychosocial wellbeing – A prospective cohort study within the Danish National Birth Cohort. (June 2020) - Herzog, C.; Homøe, P.; Koch, A.; Niclasen, J.; Dammeyer, J.; Lous, J.; Kørvel-Hanquist, A.
Abstract: Background: Otitis Media (OM) is one of the most common infections among children in developed countries and may result in temporary conductive hearing loss (HL) if accompanied by middle ear effusion (MEE). Ventilation tube insertion (VTI) is recommended as treatment for recurrent acute OM or chronic MEE with HL. HL may lead to impaired development of psychosocial skills. However, evidence for the developmental consequences of OM and the effect of VTI is inconsistent. The objectives of this study were to investigate 1) whether OM in early childhood is associated with long-term consequences of psychosocial development and 2) if VTI prevents the possible negative consequences of OM. Methods: This study examined prospectively collected data from 52.877 children registered in the Danish National Birth Cohort (DNBC). Information about previous OM-episodes and VTI was obtained through systematic follow-up interviews at seven years, and The Strength and Difficulties Questionnaire (SDQ) containing questions about psychological wellbeing was completed. Five groups were defined based on OM-exposure and the presence of VTI. Baseline characteristics were analysed, and comparison of mean SDQ-scores for the five exposure groups was conducted. Means were adjusted for à priori defined confounding factors. Results: Data from 52, 877 children in the DNBC showed an association between OM and poorer SDQ-scores. VTI was associated with an additional increase, i.e. worsening, of the SDQ-score for boys, and only a slight beneficial effect on the girls' outcome. The groups differed in their baseline characteristics in e.g. maternal education, socio-economic status, breastfeeding, and prematurity. Conclusion: Significant associations between parent-reported OM in early childhood and later psychosocial health difficulties were found. VTI did not resolve this association.